Cultural sustainability in indigenous people's festivals : cultural impact of Riddu Riddu Festival, Norway - Sarghe, Oana-Elena (2019)
The purpose of this study is twofold: first, to present festivals as a platform for preserving intangible cultural heritage. Secondly, as preserving heritage is an essential aspect of cultural sustainability, festivals as cultural events also contribute to the cultural sustainability of traditions, practices and knowledge which are transmitted from generation to generation. In the case of indigenous people, particularly Sami people in Northern Norway, the case of Riddu Riddu has proven to be a valuable arena for searching and expressing Coastal Sami identity, by influencing the way in which Sami people reflect and relate to their own heritage. Because the Sami community itself drives the development of the festival, questions of authenticity and hybridity surface as ways to combine traditions and modernity in a result relevant for the community. This qualitative study is designed to gather individual representations of change by the use of semi-structured interviews. The most significant changes in attitudes and associated meanings are analysed further in four themes: reinterpreted relations to Sami culture, festival management, intergenerational perspectives and insights on language use. Using an adjusted framework of cultural outcomes, initially tailored for cultural policy planning, the cultural impact of the festival affects how creativity, aesthetic enrichment, knowledge, diversity of cultural expressions and a sense of belonging are expressed. The broader implication of this framework, outside policy areas, is to design events and activities with a specific cultural outcome in mind.